Implementation of the Gross Up Method in the Calculation of Income Tax Article 21 Based on PP Number 58 of 2023 - Nur Rachmawati, Zaroh Winda; Priono, Hero (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
The strategy for optimizing tax burden can be pursued through the implementation of the gross-up method in the calculation of Article 21 Income Tax. This study examines the application of the gross-up method at CV T, which employs three employees with different PTKP (non-taxable income) statuses, based on the provisions of Government Regulation Number 58 of 2023. The study adopts a qualitative descriptive method with a case study approach, based on field observations, internal company documents, and informal interviews. The research findings indicate that the application of the gross-up method provides significant benefits, as the company can classify the tax allowance as an operational expense that reduces taxable income, while employees receive net income without income tax deductions. Thus, this method is considered efficient and supports tax compliance.